Respiratory metabolism of salivary glands during the late larval and prepupal development of Drosophila melanogaster - Farkaš, Robert; Sláma, Karel (Journal of insect physiology, 2015)
During the late larval period, the salivary glands (SG) of Drosophila show a cascade of cytological changes associated with exocytosis and the expectoration of the proteinaceous glue that is used to affix the pupariating larva to a substrate. After puparium formation (APF), SG undergo extensive cytoplasmic vacuolation due to endocytosis, vacuole consolidation and massive apocrine secretion. Here we investigated possible correlations between cytological changes, the puffing pattern in polytene chromosomes and respiratory metabolism of the SG. The carefully staged SG were explanted into small amounts (1 or 2μl) of tissue culture medium. The respiratory metabolism of single or up to 3 pairs of glands was evaluated by recording the rate of O2 consumption using a scanning microrespirographic technique sensitive to subnanoliter volumes of the respiratory O2 or CO2. The recordings were carried out at times between 8h before pupariation (BPF), until 16h APF, at which point the SG completely disintegrate. At the early wandering larval stage (8h BPF), the glands consume 2nl of O2/gland/min (=2500μl O2/g/h). This relatively high metabolic rate decreases down to 1.2-1.3nl of O2 during the endogenous peak in ecdysteroid concentration that culminates around pupariation. The metabolic decline coincides with the exocytosis of the proteinaceous glue. During and shortly after puparium formation, which is accompanied cytologically by intense vacuolation, O2 consumption in the SG temporarily increases to 1.6nl O2/gland/min. After this time, the metabolic rate of the SG decreases downward steadily until 16h APF, when the glands disintegrate and cease to consume oxygen. The SG we analyzed from Drosophila larvae were composed of 134 intrinsic cells, with the average volume of one lobe being 37nl. Therefore, a single SG cell of the wandering larva (with O2 consumption of 2nl/gland/min), consumes each about 16pl of O2/cell/min. A simultaneous analysis of the rate of protein and RNA synthesis in the SG shows a course similar to that found in respiratory metabolism.
Keywords: larva; Larva; Drosophila melanogaster; zvířata; Salivary glands; chromozomy hmyzu; Chromosomes, Insect; spotřeba kyslíku; biologická proměna; Basal Metabolism; Salivary Glands; exocytóza; Exocytosis; Oxygen Consumption; Metamorphosis; Metamorphosis, Biological; slinné žlázy; Microrespirometry; bazální metabolismus; Animals; Prepupal period; In vitro culture